Diagnostic Evaluations of Autism Spectrum Disorder during the COVID-19 Pandemic - Jang, Jina (J Autism Dev Disord, 2021)
A global pandemic has significantly impacted the ability to conduct diagnostic evaluations for autism spectrum disorder (ASD). In the wake of the coronavirus, autism centers and providers quickly needed to implement innovative diagnostic processes to adapt in order to continue serve patient needs while minimizing the spread of the virus. The International Collaborative for Diagnostic Evaluation of Autism (IDEA) is a grassroots organization that came together to discuss standards of care during the pandemic and to provide a forum wherein providers communicated decisions. This white paper is intended to provide examples of how different centers adjusted their standard approaches to conduct diagnostic evaluations for ASD during the pandemic and to provide insight to other centers as they go through similar challenges.